Adapting Covid-19 Pandemic by Motorcycle Dealership Digitization - Andrew Turmawan; Togar Alam Napitupulu (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Pandemic Covid-19 had brought major challenges regarding motorcycle market downturn and have-to-pay operational cost in 2020. Therefore, digitizing motorcycle dealership process is one of the strategies to improve the competitive advantage in motorcycle business. Such high investment regarding implementing information system were done by the biggest automotive players in Indonesia to achieve better cost efficiency. To evaluate the outcome of investment effectiveness, Information Economics combine with a time-motion study-workload analysis was used to analyze not only tangible benefit, but also quasi tangible and intangible benefits in hundreds of motorcycle network, involving leader, team, and front-line people in multiregional of Indonesia. Information Economics combine with workload analysis using Full Time Equivalent is used to measure the efficiency impact in organization resource after implementing the information system. The case study is proving that the investment valuation of an implemented information system should not see ROI (Return on Investment) as the only benefit, but organization workload, strategic and competitive advantage through the market competitiveness is very beneficial for business. Therefore, both financial and non-financial impact should be evaluated to have better perspective of investment.